The politics of immigration during an economic crisis: analysing political debate on immigration in Southern Europe. Issue 14 (26th October 2018) - McMahon, Simon
ABSTRACT: Since 2008, dramatic economic crises have brought falling GDP, rapidly rising unemployment and pressure on government to limit public spending to Spain and Italy. These are two countries with similar experiences of migration but quite different politics of immigration over the past two decades, with public order and security concerns coming to the fore in Italy during the 1990s and 2000s, whilst there was a general avoidance of the issue in Spain. Spain and Italy therefore provide a useful opportunity to examine the interaction between the economic crisis and political debates on immigration. Examining political debates on immigration in the parliaments of both countries from 2008 to 2011, this paper finds that during the crisis there was not a mainstream negative politicisation of immigration in these countries, despite high migration flows, rising high unemployment, aggressive austerity from government and uncertainty regarding the economy. This is explained by showing how the political debate in each country is mediated by different configurations of public opinion, institutions and discursive structures.